Life Cycle Assessment Optimization of a Shotcrete Tunnel Lining - Stepanek, P; Lanikova, I; Venclovsky, J (IOP conference series. Materials Science and Engineering, 2018)
The proposed contribution describes the formulation of the optimization design of a utility tunnel lining. The objective function is defined as a multicriterial problem and includes economic and environmental aspects associated not only with concrete member production but also with maintenance during utilization (life cycle assessment). The constraining conditions expressed by relations derived from equations of equilibrium (the solution of optimization calculations for a structure with a Winkler foundation using the Finite Element Method), the reliability conditions of a reinforced concrete structure and the continuity of deformations define the range of allowable solutions from the mathematical viewpoint. The thickness of the tunnel lining and areas of the top and bottom reinforcement in cross-sections are optimized. A method (algorithm) for obtaining a serviceable reinforcement design (via the implementation of reinforcement types) from an optimal solution is described. The obtained results are compared and analysed.